Miss Sloan' and 'Patroness' Cal Polytechnic School San Luis Obispo, Cal - Frank Aston::::::photographer::: (1908)
Clydesdales 'Miss Sloan' and 'Patroness' shown in halter by farm foreman, Samuel C. Griffith. (Published in the Polytechnic J. (v.3, n.9 June 1908) with caption 'The Clydesdales and Sam' and a note: 'Since this picture was taken the School has been so unfortunate as to lose Miss Sloan.')